ANALISIS BREAK EVEN POINT (BEP) SEBAGAI ALAT PERENCANAAN LABA PADA USAHA KULIT LUMPIA SAHABAT CAP MERAH DESA JENETALLASA KECAMATAN PALLANGGA KABUPATEN GOWA - Firdayanti Firdayanti (UNIVERSITAS DHARMAWANGSA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting Indonesia’s economy through job creation, increasing community income, and contributing to the national Gross Domestic Product (GDP). However, many MSMEs still face limitations in financial management, particularly profit planning, which may hinder business growth and reduce competitiveness. This problem is also experienced by Sahabat Cap Merah Lumpia Skin Business located in Jenetallasa Village, Pallangga District, Gowa Regency, which still faces difficulties in determining profit targets, controlling production costs, and dealing with monthly sales fluctuations. These conditions indicate the absence of structured profit planning, which may affect business decision-making. This study aims to analyze the Break Even Point (BEP) as a profit planning tool for the business. The research method used was descriptive qualitative with quantitative data in the form of cost, production, and sales data for the January–December 2024 period obtained through interviews and documentation. The results showed that fixed costs amounted to Rp385,015,000 per year and variable costs amounted to Rp244,879,654 per year. The contribution margin was Rp10,559.23 per unit with a contribution margin ratio of 75%. The break-even point was achieved at sales of 3,039 units or Rp42,539,484 per month. The Margin of Safety (MOS) ranged from 1,461 to 5,841 units, indicating that the business was in a safe condition. To achieve the profit target, the business needs to sell at least 3,986 units or Rp55,798,028 per month. In conclusion, Break Even Point analysis can be effectively used as a profit planning tool to determine minimum sales targets, control costs, and support better business decision-making for MSMEs.